Providing a psychological scale to measure COVID-19 phobia in the Indonesian version: a brief report on validation of C19P-S via Rasch Analysis - Anastasia Dewi Anggraeni; Helda Jolanda Pentury; Itsar Bolo Rangka (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2021)
Specific phobias such as COVID-19 are new and are believed to have developed rapidly since the beginning of the Pandemic established by the WHO in March 2020. Unfortunately, the development of psychological measurement tools related to COVID-19 Phobia is still inadequate in Indonesia. This study aims to validate the Indonesian version of the Phobia scale against COVID-19 (C19P-S). It was recorded that 220 respondents from various groups were involved in this study. The data collected were analyzed by means of the Rasch Model to determine the accuracy of the validated psychometric properties of the scale. The study findings show that the Indonesian version of C19P-S has sufficient psychometric properties and can measure phobia against COVID-19 in the sample group tested. Of the 20 items of the C19P-S, we recommend 18 items that are suitable for use by users of this scale.